FRI0127 Treatment Targets with First Line Biological Agents in Early and Longstanding Rheumatoid Arthritis Patients. (9th June 2015) - Conigliaro, P.; Triggianese, P.; Sunzini, F.; Duca, I.; Barba, M.; Chimenti, M.S.; Perricone, R.
Abstract : Background: Remission or low disease activity (LDA) are the main treatment targets in Rheumatoid Arthritis (RA). Different remission criteria have been developed and differ between studies. The advent of biologic disease-modifying antirheumatic drugs (DMARDs) allowed a proportion of patients to reach these goals. Objectives: We aimed at evaluating remission, sustained remission and LDA in "real life" RA patients treated with first line anti-TNF agents by different remission criteria. We evaluated the concomitant prednisone (PDN) and conventional synthetic (cs) DMARDs treatment. Methods: We analysed retrospectively remission and LDA in 298 RA patients [age 54.5±13.3 years, 242/56 female/male, 92 early RA, 206 longstanding RA, baseline disease activity by 28 joint Disease Activity Score (DAS28) 5.2±1.3, 79.6% on concomitant csDMARDs, 49.3% on PDN] treated from 2008 to 2014 in the University of Rome Tor Vergata with first line anti-TNF drugs (120 Adalimumab 40mg/other week and 178 Etanercept 50mg/weekly). Remission and LDA were evaluated according to DAS28, Simplified Disease Activity Index (SDAI) and Clinical Disease Activity Index (CDAI) at three time points: 6 months, 1 and 2 years after the start of anti-TNF. Statistical analyses were performed using McNemar and Fisher tests. Results: At 6 months remission was achieved in 18-24% of patients, at 1 year in 21-26% and at 2 years in 15-17% of cases. (Figure 1A ). No significant difference was demonstrated comparing CDAI, SDAI and DAS28 remission. Remission at two consecutive time points was detected in 17.8% (DAS28), 17.1% (SDAI) and 14.8% (CDAI) of patients, while sustained long-term remission (at the three time points) was observed in 5% (CDAI and SDAI) and 4.3% (DAS28) of patients. LDA was detected in 33-45% of patients at 6 months, in 31-42% at 1 year and in 24-31% of patients at 2 years of treatment. DAS28 allowed identifying less patients in LDA compared with CDAI at 6 months and 1 year of treatment (p=0.01 and p=0.03) (Figure 1B ). A higher number of early RA patients achieved remission than longstanding RA patients at 6 months (p<0.05 by CDAI and SDAI), 1 year (p<0.05 by DAS28 and SDAI, p=0.0001 by CDAI) and 2 years of treatment (p<0.05 by DAS28, p<0.01 by CDAI and SDAI) (Figure 1C-E ). Likewise, a higher number of early RA patients achieved LDA than longstanding RA at 1 year (p<0.01 by DAS28 and CDAI, p<0.05 by SDAI) and at 2 years (p<0.05 by DAS28 and SDAI) (Figure 1F-H ). During anti-TNF treatment a significant reduction of the number of patients on PDN was observed at 6 months, 1 and 2 years compared with baseline (p<0.0001 for all comparisons). Concomitant csDMARDs were reduced at 1 and 2 years compared with baseline (p<0.01 for both comparisons). Conclusions: RA patients treated with first line anti-TNF drugs in routine clinical care achieved remission in 15-26% and LDA in 24-45% of cases according to the various indices allowing the reduction of PDN and csDMARDs treatment. DAS28 appeared more stringent than CDAI in identifying patients in LDA. Only a small proportion of patients (5%) achieved sustained long-term remission by the various indices. Anti-TNF treatment in early RA patients allowed better results compared with those in longstanding ones. Disclosure of Interest: None declared